Peran Logika Dalam Berfikir Kritis Untuk Membangun Kemampuan Memahami Dan Menginterpretasi Informasi - Rendi Rendi; Marni Marni; Tia Neonane; Mozes Lawalata (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This study examines the role of logic in critical thinking as an effort to develop the ability to understand and interpret information. Focusing on the importance of logic in the process of critical thinking, this research explores how the use of logic can help individuals understand and interpret information more effectively. Through an examination of the concepts of logic and critical thinking, this study aims to depict the relationship between these two aspects in the context of developing the ability to understand and interpret information. By understanding the role of logic in critical thinking, it is hoped to provide deeper insights into how individuals can enhance their ability to understand and interpret information more effectively.